2011
DOI: 10.1007/s10531-011-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility predicts structural variation of Andean Polylepis forests

Abstract: High Andean mountain forests, formed almost purely by trees of the genus Polylepis, occur nowadays as scattered remnant patches of a more continuous past distribution. Apparently, the destruction of Polylepis forests has mainly been caused by millennia of human disturbance, although forest distribution may also have fluctuated according to prevailing climatic conditions. Nowadays, the remaining Polylepis forest stands are still threatened by anthropogenic disturbance, which gradually degrades the forests. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 35 publications
2
45
0
8
Order By: Relevance
“…Imatomi et al (2009) observed that 77.8 % of C. sylvestris seeds were subjected to predation or aborted (unviable) and only 20% of the viable seeds sown in a greenhouse emerged. On the other hand, young root sprouts ensure the maintenance of the population, likely due to greater resistance to physical damage by root sprouts than by seedlings (Toivonen et al 2011) and to rapid development, because their resources are drawn from the main trunk which is already established.…”
Section: Resultsmentioning
confidence: 99%
“…Imatomi et al (2009) observed that 77.8 % of C. sylvestris seeds were subjected to predation or aborted (unviable) and only 20% of the viable seeds sown in a greenhouse emerged. On the other hand, young root sprouts ensure the maintenance of the population, likely due to greater resistance to physical damage by root sprouts than by seedlings (Toivonen et al 2011) and to rapid development, because their resources are drawn from the main trunk which is already established.…”
Section: Resultsmentioning
confidence: 99%
“…The study area was selected based on the availability of high-resolution and cloud-free remote sensing data and extensive field surveys for ground truthing carried out in the area since 2006 [23]. The climate in the study area is a semi-arid tropical alpine climate, with mean annual growing season air and soil temperatures at 4450 m of 3.9 • C and 4.6 • C, respectively [6], and with low annual but high diurnal variations in temperature [15].…”
Section: Study Areamentioning
confidence: 99%
“…Both accessibility and recovery capacity are topography dependent, but only the latter is related to the ecology of the trees, whereas the former is more related to the ecology of humans and livestock. The mentioned bias is likely strongest at lower elevation due to higher anthropogenic influence [23]. However, these highly impacted areas were excluded from this study, as we focused only on treeline-forming P. subsericans stands, which are mostly of difficult access.…”
Section: Factors Other Than Topography Determining Polylepis Forest Dmentioning
confidence: 99%
“…Landscape features have been related to vegetation characteristics to support diagnostics on maturity or degradation of forest fragments (Teixeira et al 2009;Pütz et al 2011;Toivonen et al 2011). Particularly in human modified landscapes, acessibility and land use may represent relevant landscape features to explain maturity of forest fragments (Gardner et al 2010;Toivonen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in human modified landscapes, acessibility and land use may represent relevant landscape features to explain maturity of forest fragments (Gardner et al 2010;Toivonen et al 2011). Conservation strategies include preserve or manage tropical forests, even forest fragments located in human modified landscapes, to improve connectivity, increase avaliable habitat and biodiversity (Ribeiro et al 2009;Gardner et al 2010).…”
Section: Introductionmentioning
confidence: 99%